Relationship quality and objectively measured physical activity before and after implementation of COVID-19 stay-home orders. (September 2022) - Cornelius, Talea; Denes, Amanda; Webber, Katrina T; Guest, Chelsea; Goldsmith, Jeff; Schwartz, Joseph E; Gorin, Amy A
In a sample of 28 individuals cohabiting with a partner in NYC, Boston, or Chicago, this study tested whether implementation of stay-home orders to combat the spread of COVID-19 disrupted physical activity and whether high-quality romantic relationships buffered adverse effects. Participants provided FitBit data between February and October, 2020. Stay-home orders were associated with a reduction in daily step counts, B  = −1595.72, p  = 0.018, increased sedentary minutes, B  = 33.75, p  = 0.002, and reduced daily minutes of light and moderate physical activity, B  = –25.01, p  = 0.011; B  = –0.72, p  = 0.021. No moderation effects emerged.